Transformation of Syrian Refugee Family Structures in Gaziantep Province - Helsa Nasution; M. Agung Rahmadi; Al Khawarizmi; Ririn Alvionita Sitio; Syifa Salsabila Barus; Luthfiah Mawar; Nurzahara Sihombing; Nadia Saphira (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the transformation of family structures among Syrian refugees in Gaziantep, Turkey, using a meta-synthesis of 47 studies published between 2015 and 2024. The research focuses on changes in relational, economic, and normative aspects due to prolonged displacement. The findings reveal significant shifts in family dynamics, with 73.8% of families redefining traditional gender roles and 64.2% of women becoming the primary breadwinners. The divorce rate increased by 42.6%, with 38.7% of cases linked to economic pressures. Logistic regression shows a strong correlation (r = 0.78, p < 0.001) between displacement duration and family structure transformation. The study supports Heger, Boyle, and Ali’s (2010) argument about the fluidity of gender roles in forced migration but challenges Buscher’s (2011) view on the persistence of patriarchal structures. Additionally, 82.3% of families adopted more egalitarian parenting, and children's participation in education rose to 67.4%, reducing the gender gap to 8.2%. The study also identifies adaptive strategies, such as the use of communal support systems by 58.6% of families and the integration of local cultural values by 45.2%, offering insights into resilience and adaptive capacity in prolonged crises.